Deskripsi Tafsir al-Misbah dan al-Azhar Tentang Toleransi dalam al-Quran - huda, M Thoriqul; Amalia, Eka Rizki; Utami, Hendri Utami (Tribakti: Jurnal Pemikiran Keislaman, 2019)
Etymologically camos from the word tolerance (in English) which means the attitude of allowing, acknowledging and respecting the beliefs of others without the need for approval. So tolerance is a term in a social, cultural and religious contexs which means attitudes and actions that prohibit discrimination against groups that are different or cannot be accpepted by the majority in a society. Interpretation of Al-Misbah this writing uses the method of tahlili, which is the interpretation of verses per verse of the Qur’an in accrdance with the order in the mushaf. Al-Azhar’s interpretation has a style as in the science of interpretation classified into the style of adab Al-ijtima’i, namely the style of interpretation which focuses on the explanation of the verses of the koran in terms of its accurate editor, then arranges the contet in a beautiful editor editor by highlinghting the aspects of the instruction al-qur’an for life, and linking the understanding of verses with natural laws that apply in society. While in its interpretation, the format of the presentation is first, mentioning the name of the latter and its meaning, the serial number of the letter in the composition of the mushaf, the number of verses and the place where the latter was dropped. Second, include four to five verses (adjusted to the theme or group of verses) with Arabic text, which is then translated into Malay indonesian. Third, Hamka provides the code for the base of the verse and the end of the verse when it is involved in the dialectic of interpretation, it is used solely to facilitate the reader.